2017
DOI: 10.1177/0031512517725445
|View full text |Cite
|
Sign up to set email alerts
|

Space Creation Dynamics in Basketball Small-Sided Games

Abstract: Space creation dynamics (SCDs) describe actions players perform to create a scoring opportunity. This study compared SCDs and types of offense during three different three versus three (3vs.3) basketball small-sided games (SSGs) played in half court: 3vs.3 with man-to-man defense in half playing area (3vs.3), 3vs.3 with man-to-man defense in full playing area (3vs.3), and 3vs.3 with reduced shot clock (3vs.3). We also investigated the efficacy of SCDs in all SSGs and the reliability of SCDs in 3vs.3. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
(29 reference statements)
1
23
0
2
Order By: Relevance
“…Moreover, 3x3 basketball games are characterized by a shorter shot clock duration (12 s) compared to the shot clock adopted in previous basketball investigations (elite women basketball = 24 s; college basketball = 35 s). In this regard, a previous investigation demonstrated that reducing the shot clock duration during 3x3 basketball small-sided games increases the number of shot clock violations [20]. Therefore, players have much less time to finalize a ball possession and this might produce more turnovers and defensive fouls, which consequently lead to more breaks during the LT phases compared to traditional 5x5 basketball.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3x3 basketball games are characterized by a shorter shot clock duration (12 s) compared to the shot clock adopted in previous basketball investigations (elite women basketball = 24 s; college basketball = 35 s). In this regard, a previous investigation demonstrated that reducing the shot clock duration during 3x3 basketball small-sided games increases the number of shot clock violations [20]. Therefore, players have much less time to finalize a ball possession and this might produce more turnovers and defensive fouls, which consequently lead to more breaks during the LT phases compared to traditional 5x5 basketball.…”
Section: Discussionmentioning
confidence: 99%
“…The main purposes of these games are to increase the players' activity during the drills and to specify the physical demands, ensuring the dynamics of a regular game (Hill-Haas et al, 2011). Usually, SSGs use fewer players and smaller courts than official games, and the rules are adjusted to meet the tactical and physical purposes of the coach (Bredt et al, 2018;Clemente, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our findings indicate that environmental constraints and the interrelationship between game procedures promoted distinct tacticaltechnical behaviors, suggesting that the pedagogical strategy of using small-sided games for volleyball teaching should be rethought according to the objectives of teacher/coach 3,8,9 . Thus, the situational constraints inherent in the type of practice [7][8][9][10][11][12][13][14][15][16] modify the tactical-technical behavior 11 and the size of the court must be considered in the teaching and learning processes. In addition, from the ecological approach point of view, players must train and adapt to the enormous variability of actions that the context can provide in order to have more effective evolutions when experiencing these training problems 28 , as behaviors tactical tactics emerge from the context, the ecology of the game and possibilities for action 29 .…”
Section: Discussionmentioning
confidence: 80%